2019
DOI: 10.3390/w11071328
|View full text |Cite
|
Sign up to set email alerts
|

The Capacity of the Hydrological Modeling for Water Resource Assessment under the Changing Environment in Semi-Arid River Basins in China

Abstract: Conducting water resource assessment and forecasting at a basin scale requires effective and accurate simulation of the hydrological process. However, intensive, complex human activities and environmental changes are constraining and challenging the hydrological modeling development and application by complicating the hydrological cycle within its local contexts. Six sub-catchments of the Yellow River basin, the second-largest river in China, situated in a semi-arid climate zone, have been selected for this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In this model, monthly precipitation is divided into rainfall and snowfall with the upper and lower temperature criteria, using the linear partitioning method. The model calculation flowchart and formula are detailed in Guan et al [33]. Normally, in previous studies, the upper and lower temperatures were preset as 4 • C and −4 • C without calibration in flow simulation.…”
Section: Rccc-wbmmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, monthly precipitation is divided into rainfall and snowfall with the upper and lower temperature criteria, using the linear partitioning method. The model calculation flowchart and formula are detailed in Guan et al [33]. Normally, in previous studies, the upper and lower temperatures were preset as 4 • C and −4 • C without calibration in flow simulation.…”
Section: Rccc-wbmmentioning
confidence: 99%
“…The GR4J model, developed by the research group at the CEMAGREF (now IRSTEA) [35], is an empirical and parsimonious, reservoir-based model. The description of the model parallels that of Guan et al [33]. Initially, this model had only 4 parameters (shown in Table 3), and most secondary processes are represented by empirical constants, which was widely used in Europe and Australia [36,37].…”
Section: Rccc-wbmmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptation of non-conventional water resources measures (i.e., the construction of a reservoir to serve the operation of a small hydropower plant), riverbank protection measures to control flood-prone areas and the high energy demands of the area, and the effect of CC on the environment are subjects of continuous discussion at community and municipality levels. Using hydrological modeling to simulate climate change scenarios at the level of specific river catchments can be indispensable in guiding management strategy [18].…”
Section: Continuous Rainfall-runoff Model-misdc (Matlab Code) Model Smentioning
confidence: 99%
“…The same trend was given by Wang et al (2019), who found that precipitation and temperature is projected to increase in the Upper Yangze River Basin. In Yellow River Basin, Guan et al (2019) found the temperature presented a significant rising trend, but precipitation had a decline trend.…”
Section: Discussionmentioning
confidence: 97%